Colorimetric detection of Hg2+ based on inhibiting the peroxidase-like activity of DNA–Ag/Pt nanoclusters. Issue 79 (9th August 2016) - Wu, Liang-Liang; Wang, Li-Ying; Xie, Zheng-Jun; Xue, Feng; Peng, Chi-Fang
Abstract : This paper reported that the peroxidase-like activity of DNA–Ag/Pt nanoclusters (NCs) can be inhibited selectively by Hg 2+ . Abstract : This paper reported that the peroxidase-like activity of DNA–Ag/Pt nanoclusters (NCs) can be inhibited selectively by Hg 2+ . The interaction between Hg 2+ and the DNA–Ag/Pt NCs was discussed through characterization by TEM, DLS and XPS, etc. It was found that the integration of both Hg 0 and Hg 2+ to the DNA–Ag/Pt NCs resulted in the DNA–Ag/Pt NCs aggregation and the decrease of Pt 2+ content on the DNA–Ag/Pt NCs surface, which finally impaired their catalytic activity. Based on the above mechanism, a colorimetric detection for Hg 2+ was developed with a detection limit (LOD) of 5.0 nM and a linear range from 10 nM to 200 nM. The method was highly selective toward Hg 2+ over other common metal ions, low-cost and simple, which facilitated the application of detecting Hg 2+ in tap water.